Impact of psychiatric disorders on antiretroviral therapy response of patients with HIV (Research, Society and Development, 2023)
Background: Psychiatric disorders (PD) are prevalent among people living with HIV/AIDS (PLWHA). PD occurrence in PLWHA contributes to higher rates of risky sexual behaviors and non-adherence to Antiretroviral Therapy (ART). Aim: The present study aimed to analyze the influence of PD on ART response of PLWHA. Methods: Retrospective cohort of PLWHA followed at a referral center in northeast Brazil, which was classified into two groups: individuals with and without PD. Demographic, behavioral, follow-up adherence and ART response-related variables were analyzed. Results: Of the 443 patients, 5.4% had a diagnosis of PD. Depression was the most prevalent one (66.6%). Both groups were similar in regard to epidemiological and behavioral variables. Although a higher percentage of patients without PD reported 100% adherence to ART (89.3%), there were no differences when comparing service retention rates, number of ART regimens used, mean CD4 T-lymphocyte levels and presence of undetectable viral load at the last appointment. Patients with PD, however, showed lower CD4 T-lymphocyte increase. Conclusion: The incidence of PD was low, with the most prevalent one being depression. There was no difference regarding ART response when comparing the two groups, except for the magnitude of immune response (CD4 T-lymphocyte increase) of the patients with PD, which was lower.